The behavior of badminton shuttlecocks from an engineering point of view - Johansson, C.; Chang, K.; Forsgren, C.; Karlsteen, M. (Proceedings, 2018)
This was a study of the properties of a badminton shuttle. The analysed feather was made of the brand Yonex. The properties related to the trajectory were analysed by two experiments. The first experiment provided data for the trajectory by using a camera system to capture the properties of the trajectory. Position and velocity were used to draw conclusions about the deviation to the right, as seen from the hitter. The experiment generated discrete points which made it possible to plot the data, the accuracy was estimated to ±1 cm and ±0.5 m/s. The second experiment examined the rotation of the shuttle by using a high-speed camera to capture the rotation of the shuttle. By measuring the rotation at discrete distances from the hitter, the development of the rotational speed was captured, with an accuracy of ±30 rotations per minute. The experiments described and explained a connection between sideways deviation and rotation